Using Traditional Knowledge in Unpredictable Critical Events in Reindeer Husbandry. The case of Sámi reindeer husbandry in Western Finnmark, Norway and Nenets reindeer husbandry on Yamal peninsula, Yamal-Nenets AO, Russia - Eira, Rávdná Biret Márjá (Universitetet i Tromsø, 2012)
This thesis investigates in what way traditional knowledge is used when unpredictable critical events occur in Sámi reindeer husbandry in Western Finnmark, Norway and Nenets reindeer husbandry on Yamal peninsula, Russia. In addition the aim was to investigate to what extent reindeer herder’s traditional knowledge is supported by the state official governance of reindeer husbandry. In Norway each siida number of reindeer and a strategic plan for potential unpredictable events must be included in the prescriptive rules of usage which is decided by Norwegian Reindeer Husbandry Act of 2007. In Russia there is no federal law on reindeer husbandry. A qualitative research method was chosen to highlight reindeer herder’s traditional knowledge with in-depth interviews and participating observations in addition using archival sources. The findings of traditional management perspective reflect that both in Western Finnmark and on Yamal peninsula traditional knowledge is significant in reindeer husbandry, for example in response to climatic unpredictable weather events as goavvi. The results are analyzed according to Berkes’ (2008) traditional knowledge analysis. The thesis suggest a management system based on Berkes analysis model and is named Traditional management model for Sámi reindeer husbandry with focusing on traditional management and state governance perspectives. In Norway the implementation of the Reindeer Husbandry Act in 1978 seems to have constrained use of traditional knowledge in the governance of reindeer husbandry, while the Reindeer Husbandry Act of 2007 aimed to support traditional knowledge. The main finding indicates that the use of traditional knowledge in the Sámi reindeer husbandry is only partly supported today in the Norwegian governance of reindeer husbandry which in future may affect the response of unpredictable critical events. On Yamal peninsula flexible use of knowledge in a traditional management might strengthen the resilience to handle unpredictable critical events.